The Concept of the Essence of Kokutai as the Basis of the National Identity of the Japanese People - Qizi, Ravshanova Makhfurat Murod (International Journal of Psychosocial Rehabilitation, 2020)
The scientific article discusses the formation of the methodological base and philosophical categories in the framework of the Japanese cultural tradition. The significance of the research topic is determined by the dynamics of the development of the modern global world, integration processes, the growth of interaction and cooperation between different countries and regions, the strengthening of the principles of the open world, and the expansion of dialogue and communication space. The phenomenon of nationalism is one of the most relevant and debatable topics in the modern world and its origins go back centuries.